Processing and Hedonic Test of Nila Fish (Oreochromis Niloticus) and Layang Fish (Decapterus Sp.) at the Laboratory of Fishery Product Technology - Jemri*, Jemri; Wulansari Rahim, Arini Ayu (Riwayat: Educational Journal of History and Humanities, 2023)
Shredded is a long-lasting food that has high protein and has low cholesterol levels, which is made from shredded meat or separated fiber, then added spices and fried. To determine the level of preference for shredded freshwater fish and shredded seawater fish, a hedonic test was carried out with reference to 4 indicators, namely: taste, color, texture and aroma. The objectives of this Final Project are, to find out the process of making shredded fish from freshwater fish and seawater fish. Know the consumer hedonic test on shredded freshwater fish and shredded seawater fish. The stages of making shredded fish are receiving raw materials, weeding raw materials, boiling, shredding I, seasoning, cooking, pressing, shredding II and packaging. Based on the results of hedonic tests show that shredded seawater fish has a higher value with a color value of 4.1, aroma 4.8, taste 4.5 and texture 4.6 compared to freshwater fish with a color value of 4.4, aroma 4.0, taste 2.6 and texture 3.8.